Procurement, Availability, Affordability and Use of Essential Medicines and Health Supplies at Community Level in Uganda - Muhwezi, Moses; Nuwagaba, Augustus (Advances in Social Sciences Research Journal, 2015)
Purpose - The challenges associated with procurement in Uganda lead to non-availability of essential medicines and health supplies. Some citizens do not afford prescribed medicines, leading to irrational use. This paper examines procurement, availability, affordability and use of essential medicines and health supplies at community level. Design/methodology/approach – The study covered a total of 8 purposively selected districts in Uganda. Both quantitative and qualitative methods were used. The study was guided by 22 medicines and health supplies as indicator items. Using mixed methods, data was collected, analysed and interpreted in relation to the drug supply management practice. Findings – Procurement regulations were not complied with. Health units did not stock all recommended items. Stock outs were more prevalent at lower than higher health units. Affordability was found to be a problem, leading to patients bribing medical personnel to get some medicines and health supplies at cheaper prices. For all sampled respondents, all dimensions of proper use of medicines and health supplies like advice on utilization and side effects and knowledge on appropriate storage conditions for medicines and health supplies were below acceptable levels. Originality – Whereas there is extensive work on supply chain of medicines and health supplies, not enough knowledge exists which is specific to supply chain at community level for developing counties. Besides, the tracking study that combines procurement, availability, affordability and use is very insightful and a strong starting point for future theoretical work.